2016
DOI: 10.3348/jksr.2016.74.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of Trauma-Associated Pelvic Hemorrhage: Feasibility of Super-Selective Catheterization in Heavily Injured Patients as a Damage Control for Life-Threatening Pelvic Bleeding

Abstract: Purpose:To determine the efficacy of embolization with super-selective catheterization of the internal iliac arterial branches to treat heavily injured trauma patients with pelvic arterial bleeding. Materials and Methods: A retrospective analysis was performed using the medical records of 37 patients who underwent trans-arterial embolization for trauma-associated pelvic arterial hemorrhage in a regional trauma center between July 2010 and July 2013. In each patient, hemodynamic stability, embolization level, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Some authors have advocated prophylactic embolization for time-sensitive scenarios such as cases of hemodynamic instability in particularly bad clinical conditions or other associated lifethreatening medical conditions [4,25]. Instead, other authors have demonstrated that selective targeted embolization is as rapid as proximal embolization [78]. Another scenario is the hemodynamically unstable patient, without other sources of extra-pelvic bleeding and no evidence of active extravasation on angiography: the pattern of pelvic injury can also be helpful in predicting the site of arterial injury [79].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have advocated prophylactic embolization for time-sensitive scenarios such as cases of hemodynamic instability in particularly bad clinical conditions or other associated lifethreatening medical conditions [4,25]. Instead, other authors have demonstrated that selective targeted embolization is as rapid as proximal embolization [78]. Another scenario is the hemodynamically unstable patient, without other sources of extra-pelvic bleeding and no evidence of active extravasation on angiography: the pattern of pelvic injury can also be helpful in predicting the site of arterial injury [79].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increased risk of ischemia given by non-selective embolization is mitigated by the rich collateral network present in this anatomical region [1]. Other authors, however, assert that selective embolization may be carried out as quickly as proximal embolization without reducing the survival rate of trauma patients [30].…”
Section: Embolization Techniquementioning
confidence: 99%
“…Non-selective embolization, according to some authors, is indicated to minimize the procedure time when the patient is unstable or has multiple other life-threatening injuries. However, according to other authors, selective embolization for pelvic hemorrhage is not a time-consuming procedure and can be done as rapidly as proximal embolization, without lowering the survival rate for trauma victims [ 40 ].…”
Section: Treatment For Hemorrhage In Pelvic Fracture: State Of the Artmentioning
confidence: 99%